Meek as milk and large as logic: A corpus study of the non-standard poetic simile. (August 2019) - Tartakovsky, Roi; Shen, Yeshayahu
A novel distinction is proposed between two types of closed similes: the standard and the non-standard. While the standard simile presents a ground that is a salient feature of the source term (e.g. meek as a lamb), the non-standard simile somewhat enigmatically supplies a non-salient ground (e.g. meek as milk). The latter thus violates a deep-seated norm of similes and presents interpreters with unexpected difficulty, whereby the concept set up to be an exemplar of a quality is actually less than ideal to fulfil this role. The main question addressed here is how these two simile types are relatively distributed across poetic and non-poetic corpora. We elaborate the criteria for what constitutes the non-standard simile, including separating it out from adjacent phenomena like the ironic simile (e.g. brave as a mouse), and go on to explain our operational criteria for salience. Then, we report culling 329 closed similes from an anthology of poetry and 350 closed similes from two corpora of non-poetic discourse, the Corpus of Historical American English and the British National Corpus. An independent judge rated the salience of each ground-and-source pair of each of the similes, presented in randomized order. Results show that while the standard simile is found in both types of discourse, the non-standard kind is only marginally present in the non-poetic corpora but makes up over 40% of the similes in the poetic corpus. We conclude by discussing the implications of these results for theories of poetic language and literariness.